Total Body Irradiation without Chemotherapy as Conditioning for an Allogeneic Hematopoietic Cell Transplantation for Adult Acute Myeloid Leukemia - Sultan Altouri; Mitchell Sabloff; David Allan; Harry Atkins; Lothar Huebsch; Dawn Maze; Rajiv Samant; Christopher Bredeson (Case Reports in Hematology)
Current therapies for acute myeloid leukemia (AML), failing induction, are rarely effective. We report our experience in 4 patients with AML who received 16 Gy TBI prior to allogeneic hematopoietic cell transplantation (alloHCT), between June 2010 and May 2011. Patients were 20 to 55 years of age, 2 with relapsed disease and 2 with AML failing induction. An HLA-matched graft from related or unrelated donor was infused on day 0. All but one, who received a CD34+-selected graft, received methotrexate and tacrolimus +/− antithymocyte globulin, as GVHD prophylaxis. The other patient received tacrolimus alone. Neutrophil and platelet engraftment occurred at a median of 18 and 14 days, respectively. Patients were discharged at a median of 28 days. There were no unexpected toxicities in the first 30 days. One patient had cytomegalovirus (CMV) viremia and anorexia, at two months. One patient had grade 2 acute GVHD of the skin. One patient developed chronic GVHD of the eyes, mouth, skin, joints, and lung at 4 months. Two patients died from relapse of their leukemia at days 65 and 125. Two patients remain in remission beyond day 1500. 16 Gy TBI followed by an alloHCT for AML, failing induction, is feasible and tolerable.